A Review of the Concepts of Sustainable Development and the Relationship Between Sustainable Development and Human Resource Management - Wasan Kamil Afloog (International Forum of Researchers and Lecturers, 2025)
Sustaincapability is a pioneer opinion that has been receiving more and more consideration by companies; Especially since the compilation of the sustaincapability report of listed companies became mandatory. Over the past decade, establishmental sustaincapability has changed aboard centralizing on issues thus as associable accountcapability relying on preserving a well credit in the associable square and patronaging the surroundings to a strategic necessity to achieve patronagable implementation in the three economic, associable and surroundingsal squares. Is Big establishments, regardless of the sustaincapability strategy, have faced competes and worse, due to their influence on their national economy, they have cautilizated their countries to suffer problems and even crises in the associable and surroundingsal squares. Therefore, procrastination in not complying with the principles and requirements of sustaincapability increases the hidden costs of establishments and even countries and makes it more hard for them to implement it with the passage of time. For this reason, in the present article, it deals with a revision method by collecting inestablishment aboard the library and internet methods and compiled revision articles on the opinion of patronagable growth and the communication among patronagable growth and person resource handling.